2006
DOI: 10.1038/sj.emboj.7601075
|View full text |Cite
|
Sign up to set email alerts
|

A CDK-catalysed regulatory phosphorylation for formation of the DNA replication complex Sld2–Dpb11

Abstract: Phosphorylation often regulates protein-protein interactions to control biological reactions. The Sld2 and Dpb11 proteins of budding yeast form a phosphorylation-dependent complex that is essential for chromosomal DNA replication. The Sld2 protein has a cluster of 11 cyclindependent kinase (CDK) phosphorylation motifs (Ser/ Thr-Pro), six of which match the canonical sequences Ser/Thr-Pro-X-Lys/Arg, Lys/Arg-Ser/Thr-Pro and Ser/ Thr-Pro-Lys/Arg. Simultaneous alanine substitution for serine or threonine in all th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
124
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(132 citation statements)
references
References 49 publications
8
124
0
Order By: Relevance
“…More recent analyses of phosphoregulation suggest alternative regulatory paradigms involving multiple phosphorylation sites that do not need to be conserved (24). Clusters of multiple phosphorylation sites can modulate interactions (25,(47)(48)(49) or provide specific dynamic properties (50)(51)(52) and these mechanisms may not depend on the specific locations or numbers of sites (24). Consistent with this model, we found statistical evidence for constraint at the level of the cluster of consensus sites in the linker region of ORC1, despite weak constraint at the amino acid level.…”
Section: Discussionsupporting
confidence: 81%
“…More recent analyses of phosphoregulation suggest alternative regulatory paradigms involving multiple phosphorylation sites that do not need to be conserved (24). Clusters of multiple phosphorylation sites can modulate interactions (25,(47)(48)(49) or provide specific dynamic properties (50)(51)(52) and these mechanisms may not depend on the specific locations or numbers of sites (24). Consistent with this model, we found statistical evidence for constraint at the level of the cluster of consensus sites in the linker region of ORC1, despite weak constraint at the amino acid level.…”
Section: Discussionsupporting
confidence: 81%
“…These observations raise additional questions about the order of assembly of additional pre-initiation factors at origins of DNA replication. In budding yeast the Rad4 TopBP1 homologue Dpb11 has been shown to interact with both Sld2 and Sld3 and those events have been shown to be CDK-dependent and similar data have recently been reported in metazoans (6,7,8,10,11,12,49). Chromatin association of Cdc45 has been previously shown to be dependent upon Mcm10, Rad4 TopBP1 , Sld3 and the GINS complex (22,23,24,47).…”
Section: ) Predictably Mcm4supporting
confidence: 62%
“…In budding yeast Cdc45 and Sld3 associate with early firing origins in G1, prior to CDK and DDK activity, and with late firing origins in S phase (3,4). Evidence from budding yeast has demonstrated that Sld2 and Sld3 recruitment are pivotal events in replication initiation at origins and the two proteins are critical targets of the S phase CDK (5,6,7,8). Upon phosphorylation by CDK, Sld2 and Sld3 interact with distinct BRCT domains of a third protein, Dpb11, the Saccharomyces cerevisiae orthologue of human TopBP1, and that interaction enables recruitment to the pre-RC (6,7,8).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dpb11-1 mutant is temperature sensitive for growth, has slow progression of DNA replication, and shows defects in both the S phase and G 2 /M checkpoint. The fourth BRCT repeat is involved in binding Sld2, and a two-hybrid analysis showed a strong reduction in the interaction signal between Sld2 and mutant Dpb11-1 compared with the wild type (29). The minimal fourth BRCT domain ends at Leu-566, however, extensive sequence conservation continues past amino acid 583, the point of truncation in dpb11-1, until position 586 (Fig.…”
Section: A Bipartite Mec1 Activation Motif In the Unstructured C-termmentioning
confidence: 97%